The ECB, Between Conservatism and Pragmatism - Cécile Bastidon; Philippe Gilles; Nicolas Huchet (Journal of Central Banking Theory and Practice, 2016)
The 2008 and 2011 crises have durably affected the conditions of monetary policy transmission, particularly in the euro area. However, it is generally considered that the European Central Bank's (ECB) monetary policy truly became unconventional only at a late stage. Our contribution is threefold. We first show that the notion of "conventional" monetary policy, which is the reference of this assessment, is a recent theoretical construction. Secondly, the mandate of the ECB, which is its institutional expression, may raise specific difficulties in managing major financial crises, particularly with regards to the forward guidance of expectations and the commitment to an accommodative policy. Finally, the resulting policies have, at this stage, paradoxically achieved acceptable levels of macroeconomic and overall financial stability, but failed to restore a private funding supply to the banking sector enabling it to play its normal role in financing economic activity.
Keywords: E58; G01; G12; G21; 330; European Central Bank; unconventional monetary policies; generations of crises; financial stability; money markets.